Assessing The Impact Of Financial Intelligence And Technology On Digital Investment Decision - Stephanus Remond Waworuntu; Anastasya Tivani; Purwanto Purwanto; Erman Sumirat (Jurnal Inovasi Bisnis dan Kewirausahaan, 2026)
Abstract-The impact of the Internet on global society has been both rapid and transformative, bringing about significant changes in many aspects of life. Currently, Indonesia is dominated by Generation Z and Millennials, who are technologically proficient and comfortable using digital platforms. Technological advances have made it easier for these generations to invest, but this has also led to an increase in unlicensed and illegal investment schemes. The rise of illegal investment schemes in Indonesia is an indication that many Indonesians are not well-informed about the benefits and risks of investing. This study aims to examine the influence of financial intelligence such as financial literacy, financial behavior, financial experience and risk tolerance on digital investment decision with financial technology as a moderating variable. This study is a quantitative study using purposive sampling. The population consisted of millennials and Generation Z living in the Jakarta metropolitan area and the sample size was 165. The data were analyzed using moderated regression analysis. The result tells that financial literacy, financial behavior, financial experience has significant influence on digital investment decision, while risk tolerance has insignificant influence on digital investment decision. Financial technology weakens the influence of financial literacy, financial behavior, financial experience and risk tolerance on digital investment decision.